A New Framework to Support Lean Six Sigma Deployment in Smes - Galvez-Manriquez, D (Emerald Group Holdings Ltd., 2019)
Purpose: The purpose of this paper is to propose an assessment approach to evaluate the organizational capabilities to deploy a Lean Six Sigma (LSS) strategy. Design/methodology/approach: Based on a comprehensive literature review, critical success factors required to deploy LSS were defined. These key factors are evaluated by a questionnaire based on maturity grids and structured as a multi-criteria model to compute a potential LSS performance indicator. This approach is illustrated through two case studies. Findings: To promote a successful implementation of LSS in SMEs, it is necessary to consider five main critical factors. The evaluation of these factors could be achieved thanks to a multi-criterion-based maturity indicator for the LSS implementation. The case studies show that this approach allows SMEs to understand their strengths and weaknesses and thus better prepare the implementation of LSS. Research limitations/implications: The proposed tool identifies characteristics of companies leading to successful LSS implementation; but is not yet able to provide a detailed strategy to improve them. The case studies were applied to manufacturing companies; therefore, there is no evidence of conclusions in the context of services. Practical implications: The proposed methodology will help managers and practitioners to evaluate the readiness level of a company to implement LSS. Then, they could estimate the effort required to achieve the LSS deployment. Originality/value: This paper proposes a new metric of the capacity to implement the LSS successfully in SMEs: the Lean Six Sigma Global Index. This indicator is based on a survey completed by managers and supported by observable phenomena to establish a tailored diagnosis before the LSS implementation. © 2018, Emerald Publishing Limited.
Keywords: Lean Six Sigma; SMEs; AHP; Assessment tool; Maturity grid